Pemasaran Produk Kecantikan Melalui Digital Marketing Pada Saat Pandemi Covid 19 (Studi Kasus: UMKM UD. Bungan Jepun) - Lebo Wini, Elisabeth Hungaria; Wiranatha, A. A. P. A. S.; Satriawan, I K. (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 4 (2022): DesemberDO - 10.24843/JRMA.2022.v10.i04.p08, 2022)
This study was aimed to determine the implementation of digital marketing, to find out what are the most dominant variables that affect marketing of beauty product and to find out what digital marketing variables affect the marketing effectiveness of UMKM UD. Bungan Jepun. The number of respondents were obtained using the slovin method from a population of 300 and an error rate of 10% so as to produce 75 respondents. The data analysis method used descriptive statistical analysis, confirmatory factor analysis and hypothesis testing (T). Digital marketing applied by UMKM UD. Bungan Jepun, namely through: facebook (UD. Bungan Jepun), instagram (bungan. jepun), website (Ud. Bungan Jepun), whatsapp (0813-3779-0279), shopee (Bungan Jepun UD) and tokopedia (Ud. Bungan Jepun). The results of descriptive statistical analysis showed that the responses from 75 respondents on average all had a strongly agree rating where the highest value was the shopee variable with an average of 4.67 and a standard deviation of 0.671. The results of the confirmatory factor analysis showed that of the most dominant variable is the attention variable, which is seeing the Bungan Jepun beauty product advertisement on social media (Y1) with a loading factor of 0.954. The results of hypothesis testing show that the digital marketing variable that has the most influence on marketing effectiveness is the whatsapp and tokopedia variables, while the digital marketing variable that has the most influence on marketing effectiveness is the facebook variable.